Karakteristik dan Pengembangan Layanan Pendidikan Islam bagi Anak Tunadaksa di SLB Negeri 1 Sleman Yogyakarta - Wulandari, Mareta; Munandar, Arif; Azizah, Rahma Nurul; Husna, Difa’ul (Alifbata : Jurnal Pendidikan Dasar, 2025)
This study aims to understand the characteristics of educational services for children with special needs in Islamic education at SLB Negeri 1 Sleman, Yogyakarta. This study uses a qualitative approach with a case study design. Data collection techniques are observation, interviews, and documentation. The data analysis goes through three stages, namely data condensation, data presentation, and drawing conclusions. The results of the study indicate that the characteristics of students with disabilities at SLB 1 Sleman Yogyakarta are categorized as students who have difficulties in motor skills, social interaction, and emotional management. Islamic education development services that are appropriate for them are designed to be responsive to these special needs, with an emphasis on flexible and inclusive teaching approaches, which allow students to learn in a way that is easier to understand and accept. The contribution of the study is to increase insight into educational services for students with disabilities with various service approaches, including the urgency of cooperation between teachers, parents, and the community in building a conducive educational atmosphere. This study also plays an important role in increasing understanding and development of improved Islamic education services for children with disabilities while providing suggestions for more successful education methods in the days to come.